Learning Natural Science Materials Of Light Through Cooperative Learning Model Class IV SDN Tiyaran 02 - Meti Tri Hayati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
To realize the quality of learning and the quality of graduates at SDN Tiyaran 02, especially class IV, it is necessary to use one of the recommended HOTS-oriented learning models in the implementation of the 2013 Curriculum, namely the Cooperative Learning model. Cooperative Learning learning model is a teaching and learning strategy that works on attitudes or helping among others in an organized organization in groups, consisting of two or more people. After implementing integrated thematic learning with the Cooperative Learning model, the authors found that the process and student learning outcomes improved. Better than the previous lesson. When the Cooperative Learning model is applied to other learning materials, it turns out that the process and student learning outcomes are just as good. The writer concludes that this cooperative learning learning practice is successful as a best practice for HOTS learning with the Cooperative Learning model.